Expression of Erwinia uredovora Phytoene Desaturase in Synechococcus PCC7942 Leading to Resistance against a Bleaching Herbicide. - Windhovel, U. (1994)
The gene coding for phytoene desaturase of the bacterium Erwinia uredovora (crtI) was inserted into the chromosome of the cyanobacterium Synechococcus PCC7942 strain R2-PIM8. For expression of crtI in the heterologous host, two constructs with different promoters were introduced into Synechococcus. In the first, crtI was fused to the 5[prime] region of the psbA gene of the xanthophycean microalga Bumilleriopsis filiformis. The second construct carried crtI inserted downstream of the neomycin phosphotransferase II gene (nptII) from the transposon Tn5. Expression of crtI under the control of the respective promoter was shown by immunodetection of the gene product. The functionality of the heterologously expressed phytoene desaturase CRTI in the transformants was demonstrated by enzymic assays. The transformants acquired very strong resistance toward the bleaching herbicide norflurazon.